Estudo sobre uma turbina a gás instalada em uma refinaria de petróleo - Pereira, Péricles Fernando [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The gas turbine (GT) is known to have: low cost of capital over the amount of energy, high flexibility, high reliability, short delivery time, commissioning and commercial operation at the beginning and quick departure. The gas turbine is also recognized for its superior environmental performance, manifested in air pollution containment and reducing greenhouse gases (Mahi, 1994). Gas turbines in simple cycle mode (SC) have long been used by utilities to limited power generation peak. In addition, manufacturing facilities use gas turbines for power generation units on site, often in combination with the process of heat production, such as hot water and steam process. In recent years, the performance of industrial gas turbines has been improved due to significant investments in research and development, in terms of fuel to electricity conversion efficiency, plant capacity, availability and reliability. The greater availability of energy resources such as natural gas (NG), the significant reduction of capital costs and the introduction of advanced cycles, have also been a success factor for the increased use of gas turbines to load applications base (Poulikas, 2004). Open Cycle Gas Turbine with a greater degree of heat to the atmosphere may alternatively be used to produce additional electricity using a steam cycle, or to compose a cogeneration process. The combined cycle (CC) uses the heat from the gas turbine exhaust gas to increase the power output and increase the overall efficiency of more than 50% second (Najjar, 2001). The initial discovery of these cycles in the commercial power generation market was possible due to the development of the gas turbine. Only from the 1970s that gas turbine inlet temperature and therefore the exhaust gas temperature was sufficiently high to allow a better efficiency in the combined cycle ... (Complete Abstract click electronic access below)

A turbina a gás (TG) é conhecida por apresentar: baixo custo de capital em relação a quantidade de energia, alta flexibilidade, alta confiabilidade, tempo de entrega curto, comissionamento e operação comercial no início e rápido partida. A turbina a gás é também reconhecida por seu melhor desempenho ambiental, que se manifesta na contenção da poluição do ar e reduzindo os gases de efeito estufa (Mahi, 1994). As turbinas a gás no modo simples ciclo (SC) têm sido muito utilizados pelas concessionárias para geração de energia limitada de pico. Além disso, instalações industriais usam unidades de turbinas a gás para geração de energia no local, geralmente em combinação com a produção de calor de processo, tais como água quente e vapor de processo. Nos últimos anos, o desempenho de turbinas industriais a gás foi melhorado, devido a investimentos consideráveis em pesquisa e em desenvolvimento, em termos de combustível para eficiência de conversão de energia elétrica, capacidade da planta, disponibilidade e confiabilidade. A maior disponibilidade de recursos energéticos, como o gás natural (GN), a redução significativa dos custos de capital e a introdução de ciclos avançados, também têm sido um fator de sucesso para o aumento da utilização de turbinas a gás para aplicações de carga de base (Poulikas, 2004). O Ciclo aberto de Turbina a Gás com maior grau de calor para a atmosfera pode alternativamente ser usado para produzir energia elétrica adicional por meio de um ciclo de vapor ou compor um processo de cogeração. O ciclo combinado (CC) utiliza o calor dos gases de exaustão da turbina a gás para aumentar a produção de potência e aumentar a eficiência global de mais de 50% segundo (Najjar, 2001). A descoberta inicial destes ciclos no mercado de geração de energia comercial ... (Resumo completo, clicar acesso eletronico abaixo)
Keywords: Turbinas a gas; Análise energética; Petroleo - Refinarias; Gas-turbines